Estudio de factibilidad para la creación de una empresa para la obtención de abono orgánico mediante la transformación de residuos orgánicos a base de la lombricultura “Humus” (2017)
The feasibility study for the creation of a company to obtain organic manure through the transformation of organic waste based on vermicomposting was carried out by making a diagnosis of where the project was developed; Which allowed the application of a market study that evaluated from the macro to micro variables, where the conditions that the market offers to the company producing organic fertilizer were found so that it could enter with greater comfort. The target market to which the humus of worm will be directed will be the capital homes of the socio-economic strata three and four of the localities of Barrios Unidos and Teusaquillo of the city of Bogotá, to which they will be sold granulated humus In a presentation of one (1) kilogram. At the same time, a technical study was elaborated that explains what the project will need to operate and the details of the operation; Which allowed the study to know the number of workers to meet the demand of the target market, generate a mission, vision and corporate values and with regard to the requirement of the company in the area of production and in the administrative area, Which is specified in the administrative study carried out. On the other hand, a legal and environmental study was done that shows what Colombian regulations require for the company to comply with what is legally established.